1989
DOI: 10.1139/z89-426
|View full text |Cite
|
Sign up to set email alerts
|

Overview of epithelial ion-transport mechanisms

Abstract: SHUTTLEWORTH, T. J. 1989. Overview of epithelial ion-transport mechanisms. Can. J. Zool. 67: 3032-3038.The basic cellular transport mechanisms for the transepithelial uptake and elimination of sodium and chloride ions are briefly reviewed. These frequently involve processes defined as secondary active mechanisms, and the problems that this creates for their identification in epithelial systems are emphasised. It is suggested that despite the wide range of epithelial tissues involved in body fluid ion regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested that the proton pump is associated specifically with the chloride cell (Lin and Randall 1991), the pavement cell (Laurent et al 1994;Sullivan et al 1995), or both (Lin et al 1994;Lin and Randall 1995). Considerable indirect evidence suggests that C1-uptake is achieved by a Band 3 or Band 3-like C1-IHC05 exchanger located on the apical membrane of chloride cells (reviewed by McDonald et al (1989) ;Shuttleworth 1989;Avella and Bornancin 1990;Perry and Laurent 1993;Evans 1993;Marshall 1995). The existence of the C1-IHCO: exchange mechanism in the fish gill and its association with chloride cells is based exclusively on correlative studies linking chloride cell fractional surface area to the rates of C1-uptake (Perry and Laurent 1989;Laurent and Perry 1990;Perry et al 1992) or branchial net acid equivalent excretion (Goss et al 1992a(Goss et al , 1994aGoss and Perry 1994;Perry and Goss 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the proton pump is associated specifically with the chloride cell (Lin and Randall 1991), the pavement cell (Laurent et al 1994;Sullivan et al 1995), or both (Lin et al 1994;Lin and Randall 1995). Considerable indirect evidence suggests that C1-uptake is achieved by a Band 3 or Band 3-like C1-IHC05 exchanger located on the apical membrane of chloride cells (reviewed by McDonald et al (1989) ;Shuttleworth 1989;Avella and Bornancin 1990;Perry and Laurent 1993;Evans 1993;Marshall 1995). The existence of the C1-IHCO: exchange mechanism in the fish gill and its association with chloride cells is based exclusively on correlative studies linking chloride cell fractional surface area to the rates of C1-uptake (Perry and Laurent 1989;Laurent and Perry 1990;Perry et al 1992) or branchial net acid equivalent excretion (Goss et al 1992a(Goss et al , 1994aGoss and Perry 1994;Perry and Goss 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater teleosts absorb Na+ from the ambient medium against steep concentration gradients (Maetz and Garcia-Romeu, 1964; for a review, see Perry, 1997). This uptake was originally attributed to an electroneutral Na+/H+ (or NFU*) antiporter (Krogh, 1938) located in the apical membrane of the branchial epithelium (Wright and Wood, 1985;Shuttleworth, 1989; for a review, see Marshall, 1995). But several substantive observations led to this paradigm being abandoned.…”
Section: Introductionmentioning
confidence: 99%